2013
DOI: 10.1007/s12272-013-0090-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of astragalin isolated from the leaves of Morus alba L. against free radical-induced oxidative hemolysis of human red blood cells

Abstract: We evaluated the antioxidant properties of mulberry leaves extract (MLE) and flavonoids isolated from MLE. MLE was prepared by extraction with methanol. Flavonoids were analyzed by high-performance liquid chromatography. Oxidative hemolysis of normal human red blood cells (RBCs) was induced by the aqueous peroxyl radical [2,2'-Azobis (2-amidinopropane) dihydrochloride, AAPH]. MLE contained three flavonoids in the order quercetin (QC) > kaempferol (KF) > astragalin (AG). Oxidative hemolysis of RBCs induced by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 23 publications
1
51
0
Order By: Relevance
“…Isoquercitrin has been reported to have antimicrobial (25) and antioxidant (26) effects. Astragalin has also been reported to have antioxidant (27) and anti-inflammatory (28) effects. The present study also identified quercetin from a minor peak (data not shown), but its contents in extract samples were far lower than those of the other compounds of interest, with a maximum concentration of 0.28 mg/g determined.…”
Section: Discussionmentioning
confidence: 99%
“…Isoquercitrin has been reported to have antimicrobial (25) and antioxidant (26) effects. Astragalin has also been reported to have antioxidant (27) and anti-inflammatory (28) effects. The present study also identified quercetin from a minor peak (data not shown), but its contents in extract samples were far lower than those of the other compounds of interest, with a maximum concentration of 0.28 mg/g determined.…”
Section: Discussionmentioning
confidence: 99%
“…The most abound compounds were ellagic acid, isoquercitrin and astragalin for NL and FL, with the contents of 52.62 70.05, 74.14 70.01, 71.21 70.01 mg/g and 33.73 70.33, 45.76 70.02, 25.437 0.03 mg/g, respectively. All the compounds had been proved with various bioactivities, including antioxidant and anti-inflammatory (Vattem and Shetty, 2005;Soromou et al, 2012;Choi et al, 2013;Valentova et al, 2014). Ellagic acid also exhibited anti-allergic activity in several models (Xue et al, 2012).…”
Section: Qualitative and Quantitative Analyses Of Nl And Flmentioning
confidence: 99%
“…It is widely found in tea and has been used to treat many diseases as a traditional Chinese medicine for a long time. Several groups have confirmed that AG exhibits a number of biological properties, including anti-inflammatory, antioxidant, and anti-atopic dermatitis effects [1114]. In addition, AG can attenuate lipopolysaccharide (LPS)-induced inflammatory responses by suppressing the NF-кB signaling pathway [15].…”
Section: Introductionmentioning
confidence: 99%